Influences of the North Atlantic oscillation on precipitation variability and change in Turkey - Türkeş, M.; Erlat, E. (Societa italiana di fisica, 2006)
The anomalous circulations at 500-hPa geopotential level during the extreme North Atlantic Oscillation Index (NAOI) phases were investigated in order to explain atmospheric causes of the changes in precipitation of the 78 stations of Turkey during the extreme NAOI phases. We arranged and analysed the 500-hPa height data of the 231 grid points for a large region delimited by the 40◦ W and 60◦ E longitudes and by the 20◦ N and 70 ◦ N latitudes. The main conclusions of the study are as follows: 1) Annual, winter, spring, autumn and partly summer composite precipitation means are mostly characterised by wetter than long-term average conditions during the negative NAOI phase, whereas the positive NAOI responses mostly exhibit drier than long-term average conditions annually and in all seasons except summer. 2) Spatially coherent and statistically significant changes in the precipitation amounts during the extreme NAOI phases are more apparent in the west and mid Turkey. 3) The 500-hPa circulation corresponding to the negative NAOI phase brings above long-term average precipitation to Turkey in winter, spring and autumn and annually, associated with the NAO pattern in which the 500-hPa geopotential level is anomalously high in the area of the Icelandic Low and anomalously low across the regions of the Azores High and the Europe in general. 4) Contrary, the NAO pattern over the North Atlantic and the Europe is responsible for the drier than long-term average precipitation conditions in Turkey during the positive NAOI phase, when the 500-hPa geopotential level is anomalously low over the area of the Icelandic Low and the anomalously high across the subtropical and mid-latitude north-east Atlantic and the Europe regions.